Salvage endoscopic submucosal dissection in patients with local failure after chemoradiotherapy for esophageal squamous cell carcinoma. (September 2013) - Takeuchi, Manabu; Kobayashi, Masaaki; Hashimoto, Satoru; Mizuno, Ken-ichi; Kawaguchi, Gen; Sasamoto, Ryuta; Aoyama, Hidefumi; Aoyagi, Yutaka
Abstract: Objective. For locoregional failure after chemoradiotherapy (CRT) in patients with esophageal squamous cell carcinoma (ESCC), salvage esophagectomy and endoscopic mucosal resection have disadvantages, such as a high morbidity rate and a high local recurrence rate, respectively. The aim of this study was to clarify the efficacy of salvage endoscopic submucosal dissection (ESD) for locoregional failure of CRT. Methods. A total of 19 lesions in 19 patients were treated with salvage ESD; 15 lesions were local recurrences at the primary site and 4 lesions were residual. All lesions were intramucosal or submucosal tumors without metastases. A case-control study was retrospectively evaluated to clarify whether the clinical outcomes of salvage ESD were equivalent to those of control primary ESD. Results. No significant differences were observed between salvage ESD and primary ESD in short-term outcomes, including procedure time. For salvage ESD, the complete en bloc resection rate was 94.7% (18 of 19), and no severe complications were observed. At a median follow up of 54.6 (range: 5–98) months after salvage ESD, the local recurrence rate was 0%. However, three patients (15.8%) died due to lymph node and distant metastases and six patients (31.5%) died from other diseases, including radiation pneumonitis, pyothorax or respiratory failure with no recurrence of ESCC. The 3-year overall survival rate for all 19 patients was 74%. Conclusions. ESD represents an acceptable treatment option for recurrent or residual ESCC because of its improvement in local control, when local failure after CRT is limited to the submucosal layer without metastases.